Empowering Communities Through Educational Outreach Programs in MTS Al-Amin Kampung Pajak - Nurfitriani M. Siregar (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2024)
This study explores the role of educational outreach programs implemented by MTS Al-Amin Kampung Pajak in empowering the local community. Using a qualitative descriptive approach, the research highlights how the school engages students, parents, and community members through activities such as tutoring sessions, literacy programs, parenting workshops, and youth leadership training. Data were collected through interviews, observations, and document analysis, involving various stakeholders, including educators, students, and community leaders. The findings indicate that these outreach initiatives have enhanced educational engagement, strengthened school-community relationships, and fostered the personal development of students. Despite challenges related to limited resources and sustainability, the programs have shown significant positive outcomes and serve as a model for community-based educational efforts in rural areas. This study emphasizes the potential of schools to act as agents of social change through inclusive, context-driven outreach strategies.